The Application of Pulsed Magnets for Investigations of Electrical Properties of Semiconductors and Manganites - Novickij, J. (Elektronika ir Elektrotechnika, 2007)
The system for high magnetic field generation up to 50 T was developed and applied for measurements of resistance, concentration and mobility of free charge carriers of semiconductors and manganites. High frequency interferometer had expanded ranges of measurements and specimens of InSb, CdHgTe samples were investigated at room and liquid nitrogen temperature. Magnetoresistance of epitaxial and polycrystalline films was measured by two electrodes method. The resistance response to high magnetic field pulses up to 50 T was studied for thin films of LaCaMnO, Bi, BiSb with different magnetic and electric properties. Polycrystalline La-Ca-MnO films have no saturation effects in high magnetic fields and can be used to measure absolute value of the fields up to 35 T. Axial magnetic field was estimated by analytical and numerical methods and verified experimentally. Numerical analysis of pulsed magnets was performed by the finite element method. New constructing materials were applied in pulsed magnet design and multilayer construction of metal-matrix Cu-Nb micro composite wire wounded Zylon-epoxy composite reinforced inductor was developed. Ill. 8, bibl. 12 (in English, summaries in English, Russian and Lithuanian).